The Potential of Rhizophagus intraradices and Trichoderma asperellum to Induce Shallot Resistance against Twisted Disease - Hertina Artanti; Tri Joko; Susamto Somowiyarjo; Suryanti Suryanti (Jurnal Perlindungan Tanaman Indonesia, 2022)
Twisted disease caused by Fusarium spp. is one of the primary diseases on shallots with potency to cause enormous losses by causing stunting and bulb rot. One alternative disease control is the induction of plant resistance since the seed stage. The aim of this study was to determine the content of salicylic acid, jasmonic acid, and phenolic compounds of shallot bulb seeds coated with biological control agents as a resistance response to twisted disease. The shallot cultivar used was Crok kuning. The treatments used in this study were the type of biological control agents, including Rhizophagus intraradices and Trichoderma asperellum, combined with and seed coating application time (one month before planting and simultaneously at planting). Biological control agents in the form of powder formulation applied as seed coating material and seeds were stored for one month before planting. The results showed that application of biological agents delayed the occurrence of the twisted disease symptoms. The salicylic acid content from plant treated with R. intraradices at the time of planting was slightly higher than the control. The jasmonic acid content in T. asperellum plants treated at planting was higher than then control. Total phenolic content from plants treated with T. asperellum at planting time was higher than the control. In general, application of biological control agent as seed coat did not result in significant increase in salicylic acid, jasmonic acid nor the phenolic compounds, compared to the pathogen infected control.